The Implementation of the Game-Based Learning Method to Improve Learning Activities of Grade X Students in Sociology Learning at SMA Cendekia Pasaman Barat - Yenni Melia; Yenita Yantim; Felia Siska; Jamiah Nurul Husna (LPPM Universitas PGRI Sumatera Barat, 2025)
This research was motivated by the low learning activity of Grade X students in Sociology subjects at SMA Cendekia Pasaman Barat. The objective of this study was to analyze the implementation of the Game-Based Learning method in improving students' learning activity. The method used was Classroom Action Research (CAR) as formulated by John Elliot, which consists of four stages: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. The research data were collected through observations of students’ learning activities and assessments of four activity indicators: listening, reading, writing, and participation. The study was conducted in two cycles. In Cycle I, the average score for listening activity was 67.37, which increased to 88.70 in Cycle II (an increase of 31.77%). Reading activity improved from 65.38 to 90.12 (an increase of 37.84%), writing activity rose from 73.90 to 90.65 (an increase of 22.66%), and student participation increased from 65.77 to 89.69 (an increase of 36.36%). Overall, the average student learning activity increased from 68.1% in Cycle I to 89.79% in Cycle II. These results indicate that the research objectives have been successfully achieved. In conclusion, the implementation of the Game-Based Learning method in Sociology learning has been proven to enhance the learning activity of Grade X students at SMA Cendekia Pasaman Barat in terms of percentage.